2016
DOI: 10.1016/j.jtho.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Effusions from Patients with Mesothelioma Induce Recruitment of Monocytes and Their Differentiation into M2 Macrophages

Abstract: These results demonstrate the implication of CCL2 in MPM pathogenesis and designate M-CSF as a new potential biomarker of MPM. This study also identifies CCL2 and colony-stimulating factor 1 receptor/M-CSF as interesting new targets to modulate pro-tumorigenic properties of the tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 27 publications
3
70
0
Order By: Relevance
“…[3][4][5][6][7][8][9] Several cytokines accumulated in the pleural effusion of MPM patients promote the M2 polarization of macrophages. 10,11 M2/M3-macrophages and Gr-MDSC of MPM patients, as well as MPM cells reduce the proliferation of heterologous CD8a molecule-positive (CD8 þ ) T lymphocytes, by producing immunosuppressive mediators such as reactive oxygen species (ROS), nitric oxide (NO) and kynurenine. 3,4,7,10,[12][13][14] MDSCs are killed by active CD8 þ T lymphocytes, whereas either Tregs and MDSCs reduce CD8 þ T lymphocyte activity and memory CD8 þ T lymphocyte recruitment, inducing a vicious immunosuppressive circle.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Several cytokines accumulated in the pleural effusion of MPM patients promote the M2 polarization of macrophages. 10,11 M2/M3-macrophages and Gr-MDSC of MPM patients, as well as MPM cells reduce the proliferation of heterologous CD8a molecule-positive (CD8 þ ) T lymphocytes, by producing immunosuppressive mediators such as reactive oxygen species (ROS), nitric oxide (NO) and kynurenine. 3,4,7,10,[12][13][14] MDSCs are killed by active CD8 þ T lymphocytes, whereas either Tregs and MDSCs reduce CD8 þ T lymphocyte activity and memory CD8 þ T lymphocyte recruitment, inducing a vicious immunosuppressive circle.…”
Section: Introductionmentioning
confidence: 99%
“…These events trigger a long-lasting inflammation, which can enhance DNA damage for the production of free radicals and inflammatory cytokines [9]. The long-lasting inflammation caused by MM and the poor response to therapeutics might be due to the ability of MM cells to subvert host immune response [10, 11]. The knowledge of MM pathophysiology might influence MM patients therapy and survival [4, 1214].…”
Section: Introductionmentioning
confidence: 99%
“…19 It has been demonstrated that pleural effusions from MM patients induce recruitment of monocytes and influence their differentiation into M2 macrophages. 20 These macrophages promote the development and metastatic capacity of tumors due to the production of protumor factors like the enzyme arginase 1,21 and a larger M2 component of the total macrophage count is inversely correlated with survival. [22][23][24] The role of galectin-9 in MM remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%